Effect of the Subsurface Drain Parameters on Water-salt Transport Based on HYDRUS-2D - LIU Luyao; ZHANG Jinlong; ZHANG Kai; JIA Lin; ZHANG Di; NIE Axiu (Renmin Zhujiang)
In order to study the effect of the subsurface drain parameters on water-salt transport,this paper performs the field test in typical experimental area selected from Binhai New Area of Tianjin,China,calibrates and verifies the simulation effect of HYDRUS-2D by experimental data,and simulates the water-salt transport under different subsurface drain parameters by the validated model.The simulation results show that:HYDRUS-2D can well simulate water-salt transport of soil under the condition of subsurface drainage.When the depth of subsurface drains is kept unchanged,the larger the subsurface drains is spaced,the higher the water and salt are contained in the soil after leaching.When the spacing of subsurface drains is kept unchanged,the deeper the subsurface drains are,the lower the water and salt are contained in the soil after leaching.Among the 12 simulated subsurface drain scenarios,under the combined parameters of 140 cm depth (maximum) and 300 cm spacing (minimum),the salt of soil profile is 0.47~7.81 g/kg (minimum).Therefore,when the subsurface drain technology is applied to the improvement of saline-alkali soil,it is necessary to reduce the spacing of the subsurface drains or increase the depth of the subsurface drains to improve the leaching effect.